2020
DOI: 10.3389/fmolb.2020.608368
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Development of a Novel 4-Gene Immune-Related Signature to Predict Osteosarcoma Prognosis

Abstract: Osteosarcoma (OS) is a malignant disease that develops rapidly and is associated with poor prognosis. Immunotherapy may provide new insights into clinical treatment strategies for OS. The purpose of this study was to identify immune-related genes that could predict OS prognosis. The gene expression profiles and clinical data of 84 OS patients were obtained from the Therapeutically Applicable Research to Generate Effective Treatments (TARGET) database. According to non-negative matrix factorization, two molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…Recently, the advancements and applications in bioinformatics tools made it easy to mine the potential gene signatures associated with the OS and prognosis of the cancers including osteosarcoma from publically available databases such as TCGA, TARGET, and GEO ( Cao et al, 2020 ; Chen et al, 2020 ; Song et al, 2020 ; Wen et al, 2020 ; Xiao et al, 2020 ; Yang et al, 2021 ). Various signature genes have been found associated with the OS of osteosarcoma patients and tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the advancements and applications in bioinformatics tools made it easy to mine the potential gene signatures associated with the OS and prognosis of the cancers including osteosarcoma from publically available databases such as TCGA, TARGET, and GEO ( Cao et al, 2020 ; Chen et al, 2020 ; Song et al, 2020 ; Wen et al, 2020 ; Xiao et al, 2020 ; Yang et al, 2021 ). Various signature genes have been found associated with the OS of osteosarcoma patients and tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more and more studies are involved. For example, in the nine studies (Cao et al, 2020;Chen Z. et al, 2020;Song et al, 2020;Wen et al, 2020;Xiao et al, 2020;Yu et al, 2020;Zhu et al, 2020;Fu et al, 2021;Yang et al, 2021) we included in the study based on the inclusion criteria, they all looked for potential survival-related OS gene signatures from public datasets.However, after we validated them in the training and validation cohorts, we found that the nine-gene signature we generated was superior to others in predicting OS prognosis. Among the nine studies, the one by Yang et al (2021)revealed a gene signature that closely resembled ours.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also validated that low-risk OS patients had significantly higher CD79A expression 32 . In addition, Cao et al 33 demonstrated that APBB1IP may act as a key to predicting OS prognosis and new biomarkers are of great significance for understanding the therapeutic targets of OS. Fan et al 34 clustered patients based on the immune cell infiltration content to identify a 9-prognostic gene signature gene model, including PLD3 for OS microenvironment exploration.…”
Section: Discussionmentioning
confidence: 99%